1985
DOI: 10.2307/1129751
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Auditory Temporal Acuity in Children

Abstract: The development of auditory temporal acuity was studied in 56 children aged 6-12 years and compared with that of 8 adults. Acuity was measured by determining the minimum detectable duration of a brief cessation in a noise band with the 2-alternative forced-choice method. For detection of gaps in a broadband noise, acuity improved significantly with age and reached adult values by 11 years. The minimum detectable duration was significantly shorter at higher levels of the noise. For narrow-band noises, acuity al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
22
4

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(31 citation statements)
references
References 0 publications
3
22
4
Order By: Relevance
“…The absolute magnitude of the temporal resolution in children estimated in the present study and Bishop et al [19] is considerably larger (between 50 and 200 ms) than with previous estimates using behavioral gap detection tasks (between 3 and 40 ms) [4-6,26,27]. In adults, the elicitation of the P1-N1-P2 complex has been shown to relate to behaviorally determined gap detection thresholds, with attenuation of the response to the second tone when presented at subthreshold gap durations [28].…”
Section: Discussioncontrasting
confidence: 73%
“…The absolute magnitude of the temporal resolution in children estimated in the present study and Bishop et al [19] is considerably larger (between 50 and 200 ms) than with previous estimates using behavioral gap detection tasks (between 3 and 40 ms) [4-6,26,27]. In adults, the elicitation of the P1-N1-P2 complex has been shown to relate to behaviorally determined gap detection thresholds, with attenuation of the response to the second tone when presented at subthreshold gap durations [28].…”
Section: Discussioncontrasting
confidence: 73%
“…The lack of significant differences between groups for the control trials (e.g., one-flash/one-beep) indicates that the difference in the temporal window size between groups is unlikely to be due to differences in response bias. While the tendency to report one flash in the two-flashes/zero-beeps condition across both children with ASD and TD suggests that visual temporal acuity may be lower in children relative to adults (Irwin et al 1985; Hautus et al 2003; Smith et al 2006), the lack of differences between groups suggests that developmental differences in visual temporal acuity do not play a role in the highlighted perceptual differences between children with and without ASD. Although our results are in accord with a previous study showing intact integration of low-level visual and auditory stimuli in individuals with ASD (i.e., that integration of multisensory information does occur) (Van der Smagt et al 2007), we have refined our understanding by showing for the first time alterations in the temporal constraints within which audiovisual stimuli are bound in children with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, several studies have suggested that some auditory tasks, such as frequency discrimination , discrimination of auditory spectra (Allen & Wightman, 1992), discrimination of low frequency tones (Maxon & Hochberg, 1982) and intensity coding (Buss, Hall & Grose, 2006), require several years to become adult-like. More relevant for our task is that children have poorer auditory temporal skills than adults (Wightman, Allen, Dolan, Kistler & Jamieson, 1989) and various psychophysical tasks suggest that their ability to distinguish rapidly presented auditory inputs continues to develop until early adolescence (Gori, Sandini & Burr, 2012;Hall & Grose, 1994;Hartley, Wright, Hogan & Moore, 2000;Irwin, Ball, Kay, Stillman & Rosser, 1985;Walker, Hall, Klein & Phillips, 2006). Experimental evidence suggests that motor coordination also develops late (Jansen-Osmann, Richter, Konczak & Kalveram, 2002;Konczak, Borutta, Topka & Dichgans, 1995;Konczak & Dichgans, 1997;von Hofsten, 1991).…”
Section: Discussionmentioning
confidence: 99%